Structure of Forensic Characteristics of Murdering Hostages or Kidnapped Persons - T. V. Bilyk (Law and Safety)
The concept and structure of forensic characteristics of crimes against human life and health have been analyzed. Based on the conducted study, the author has offered to define the forensic characteristics of a crime as the system of information about certain types of crimes with a structure consisting of a set of forensically significant elements that help the fastest investigation of the crime.